Engaged employees or happy employees? What say you / Azfahanee Zakaria ... [et al.] - Zakaria, Azfahanee; Sabir Ahmad, Sarah; Alhady, Syed Mohammed (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Today, more than ever, organizations rely on employees to achieve their long-term or short-term goals. However, the discussion is on the matter of what kind of employee does an organization needs to have. Previously, organizational holders or leaders are keen to have employees who are happy at work. This is because they foresee that employees who are happy at work would reflect positively to the productivity as well as the work culture of the organization. However, with the pinching of staff from fellow competitors, organizational holders are working on nurturing engaged employees as compared to happy employees. Why is it so?